2014
DOI: 10.1136/neurintsurg-2013-011040
|View full text |Cite
|
Sign up to set email alerts
|

Proximal to distal approach in the treatment of tandem occlusions causing an acute stroke

Abstract: A tandem occlusion of the carotid artery at the bifurcation with a concomitant intracranial occlusion is a relatively rare and complex presentation of acute stroke. We have found that addressing the proximal lesion first and covering it with a stent prior to performing distal thrombectomy appears to be a safe and effective option in the treatment algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 23 publications
3
66
1
2
Order By: Relevance
“…This study showed a primary endpoint of recanalization without a sICH in 85% of patients (17/20). Our results were in accordance with results of previous similar studies (Table 3) 7, 8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25 . Furthermore, this study showed rates of recanalization, sICH, and mortality that were similar to those found in recent randomized trials on thrombectomy for acute stroke 2,3,4,5 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study showed a primary endpoint of recanalization without a sICH in 85% of patients (17/20). Our results were in accordance with results of previous similar studies (Table 3) 7, 8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25 . Furthermore, this study showed rates of recanalization, sICH, and mortality that were similar to those found in recent randomized trials on thrombectomy for acute stroke 2,3,4,5 .…”
Section: Discussionsupporting
confidence: 83%
“…Carotid tandem occlusions are defined as both extra-cranial occlusion or stenosis of the internal carotid artery (ICA) and downstream intracranial vessel occlusion, which comprises a subgroup of patients that usually present poor recanalization rates under IVT and poor clinical outcomes 6 . Despite of the lack of clinical data from randomized trials on the best management course of acute carotid tandem occlusions, a combined recanalization strategy by means of carotid artery stenting and mechanical thrombectomy has recently shown promising results 7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25 . We aimed to assess the clinical and radiological data of patients who underwent carotid artery stenting (CAS) and endovascular treatment of acute ischemic stroke due to carotid tandem occlusions.…”
mentioning
confidence: 99%
“…There is no consensus among the neurointerventionalists in regards to the sequence of treating these lesions in acute settings. Many [12,14,15,17,24] have advocated the proximal-to-distal approach with carotid stenting prior to intracranial thrombectomy, while some [11] recommend intracranial revascularization first with both techniques having their variations, advantages and shortcomings. In our series, the choice of treatment strategy was at the discretion of the operator and varied with the evolution of thrombectomy techniques and available armamentarium.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published cohort studies indicate that tandem stenosis/occlusions of the ICA/MCA can be treated with acute stenting of the extracranial internal carotid and stent-retriever mechanical thrombectomy in the MCA with a reasonable risk profile. (36)(37)(38)(39)(40)(41)(42)(43)(44) Acute stenting of occlusions of the extracranial ICA resulted in a higher recanalization rate (87% vs 48%, p=0.001) and favorable outcomes (68% vs 15%, p<0.001) as well as lower mortality (18% vs 41%, p=0.048) when compared to intra-arterial thrombolysis. (39) Longer clot length as measured on thin-section NCCT has been associated in several studies with low probability of successful recanalization with IV tPA (45)(46)(47), raising the possibility that this group might derive greater benefit from EVT.…”
Section: Which Imaging Selection Criteria Define Candidates For Additmentioning
confidence: 99%